River and channel revetments a design manual - Escarameia, Manuela (Thomas Telford, 1998)
This guide provides an extensive compilation of the characteristics of major revetment systems and gives independent advice on the choice of the most suitable type or types. Design formulae based on research from the late 1990s are included.